2001
DOI: 10.1038/sj.ejcn.1601158
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of linoleic acid in healthy subjects after intake of a single dose of 13C-linoleic acid

Abstract: Objective: To investigate the in vivo oxidation of 13 C18X2n-6 and its conversion into longer-chain polyunsaturates (LCPs) in healthy subjects. Design: Blood samples were collected from six subjects before (fasted) and 7, 11 (non-fasted), 24, 48, 72, 168 and 336 h (fasted) after ingestion of a single bolus of 45 mg uniformly labeled 13 C18X2n-6 dissolved in 8 g olive oil. In three subjects, breath was also sampled and CO 2 production measured every hour during the ®rst 12 h. Subjects consumed their habitual di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…Our results concerning the quantitative recovery of 13 C in breath CO 2 during the first 24 h postdose and the rank order of oxidation of these four common dietary fatty acids agree with similar previously published results (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Tracer studies reporting breath data do not often extend beyond 24 h, but in 22 of the 24 breath tracer profiles in the present study, 13 C enrichment in breath CO 2 was still above baseline at 168 h (8 days) postdose.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our results concerning the quantitative recovery of 13 C in breath CO 2 during the first 24 h postdose and the rank order of oxidation of these four common dietary fatty acids agree with similar previously published results (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Tracer studies reporting breath data do not often extend beyond 24 h, but in 22 of the 24 breath tracer profiles in the present study, 13 C enrichment in breath CO 2 was still above baseline at 168 h (8 days) postdose.…”
Section: Discussionsupporting
confidence: 82%
“…Maximal incorporation of tracer into plasma ranged from 3% to 8% depending on the tracer administered. The 3 and 6 long-chain PUFAs in plasma had a maximum value of less than 0.1% of the administered dose, values that agree with other recent data (22)(23)(24)(25)(26)49). These net desaturation chain-elongation values are derived from the plasma pool but should at least qualitatively mirror the tissue incorporation of these fatty acids and their long-chain products.…”
Section: Downloaded Fromsupporting
confidence: 81%
See 1 more Smart Citation
“…However, other papers on human concluded that increasing dietary LA has no effect on increase of plasma phospholipid ARA level, or even may have an inverse relationship (Adam et al, 2003(Adam et al, , 2008Liou and Innis, 2009;Liou et al, 2007;Rett and Whelan, 2011;Thijssen and Mensink, 2005). The possible reason for no response of tissue ARA content by dietary increasing LA in those studies was considered to be related to fractional conversion from LA to ARA and limited catalysis of Δ6 Fad on LA (Demmelmair et al, 1999;Rett and Whelan, 2011;Vermunt et al, 2001). Present study has suggested that abalone has certain conversion of dietary LA to muscle ARA.…”
Section: Discussionmentioning
confidence: 90%
“…GLA is then converted to DGLA and then to arachidonic acid (AA). In a single-dose study of radio-labeled LA metabolism in healthy subjects, the percent of LA recovered as AA was very low (0.05% of the radio-labeled dose) [10].…”
Section: Discussionmentioning
confidence: 94%